Systemic Approaches for Professional Development on Diverse Learners in Rural Communities - Elizabeth Thorne Wallington; Adrienne Johnson (Educational Considerations, 2022)
While rural communities are not monolithic, many have seen recent shifts in demographics from historically homogenous populations to more racially, culturally, and linguistically diverse residents (e.g. Sharp & Lee, 2017; Brenner, 2016). Without clear systems for addressing such changes, reactionary policies to address the accompanying conflict can establish marginalized communities, deficit-based perspectives, and structural inequities (Lee & Sharp, 2017). As an alternative approach, this paper outlines promising practices for systemic approaches to addressing the ongoing professional development needs for teachers in rural communities who are supporting students from increasingly diverse backgrounds. These practices provide the support and professional development that is necessary to meet emerging student needs and strengthen educators’ self-efficacy (Flores et al., 2015; O’Neal et al., 2008). The research presented demonstrates that there is a high degree of variability in the demographics of individual districts across the urban-rural spectrum, and not all certification policies have equal efficacy. By empowering districts to meet their teachers’ and students’ needs, local control can be used efficiently and effectively through flexible state policies.
Keywords: ELs; GIS; rural; professional development